2020
DOI: 10.4324/9780429470035
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Greek Manuscripts in the Library at Wellcome Collection in London

Abstract: List of figures ix Preface xi Notes on contributors xii Note to the reader xv The Wellcome Greek Collection 1 PETROS BOURAS-VALLIANATOS 1 Greek manuscripts in the Library at Wellcome Collection: Owners and cataloguers 12 VIVIAN NUTTON 2 The clinical method of the anonymous of Paris 25 ORLY LEWIS 3 Wellcomensis MS.MSL.14 as a therapeutic handbook 54 BARBARA ZIPSER 4 The language of iatrosophia: A case-study of two manuscripts of the Library at Wellcome Collection (MS.4103 and MS.MSL.14) 66 TINA LENDARI AND IO M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(11 citation statements)
references
References 30 publications
0
0
0
Order By: Relevance
“…A similar treatment is found in Albert the Great's De Animalibus (Animals), 39 which is, like Barhebraeus's writing on the subject, primarily influenced by both Aristotle and Avicenna and will be mentioned here briefly only for the sake of comparison. Besides these shared sources, Albert is not only a representative of the Medieval Latin tradition, but also roughly contemporary with Barhebraeus.…”
Section: Excurses: Albert the Great Pliny The Elder And Ibn Abī L-ash...mentioning
confidence: 74%
See 4 more Smart Citations
“…A similar treatment is found in Albert the Great's De Animalibus (Animals), 39 which is, like Barhebraeus's writing on the subject, primarily influenced by both Aristotle and Avicenna and will be mentioned here briefly only for the sake of comparison. Besides these shared sources, Albert is not only a representative of the Medieval Latin tradition, but also roughly contemporary with Barhebraeus.…”
Section: Excurses: Albert the Great Pliny The Elder And Ibn Abī L-ash...mentioning
confidence: 74%
“…38 This model had an error rate of 9.70% which is not too bad. However, this model was not suitable for further use since we made some rookie mistakes: We did not pay especially close attention to the baselines, 39 but drawing those precisely from the exact beginning to the end of every line is crucial to getting good results from the text recognition process. In addition, it is suggested that you use almost perfect transcriptions for the HTR training, as every mistake in the transcription can falsify the actual result.…”
Section: Htr Trainingmentioning
confidence: 99%
See 3 more Smart Citations